2022
DOI: 10.3389/fnmol.2021.829564
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Spiral Ganglion Neuron Regeneration as a Therapeutic Strategy in Sensorineural Hearing Loss

Abstract: In the mammalian cochlea, spiral ganglion neurons (SGNs) are the primary neurons on the auditory conduction pathway that relay sound signals from the inner ear to the brainstem. However, because the SGNs lack the regeneration ability, degeneration and loss of SGNs cause irreversible sensorineural hearing loss (SNHL). Besides, the effectiveness of cochlear implant therapy, which is the major treatment of SNHL currently, relies on healthy and adequate numbers of intact SGNs. Therefore, it is of great clinical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Auditory neurons are particularly relevant targets in the context of cochlear implantation, which remains, thus far, the only available solution for deaf patients. Therefore, spiral ganglion regeneration has recently gained increased attention as a therapeutic strategy in this context [ 34 ]. To date, stem cell transplantation [ 35 , 36 ] and neuronal conversion from glial cells [ 37 , 38 , 39 ] are the two main strategies employed for SGN regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory neurons are particularly relevant targets in the context of cochlear implantation, which remains, thus far, the only available solution for deaf patients. Therefore, spiral ganglion regeneration has recently gained increased attention as a therapeutic strategy in this context [ 34 ]. To date, stem cell transplantation [ 35 , 36 ] and neuronal conversion from glial cells [ 37 , 38 , 39 ] are the two main strategies employed for SGN regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Spiral ganglion neurons (SGNs) in the mammalian inner ear are the first neural element in the auditory conduction pathway, as they acquire and deliver acoustic information from cochlear hair cells (HCs) to the central nervous system, thereby allowing the establishment of auditory cognition [ 1 ]. As terminally differentiated cells, SGNs cannot regenerate by themselves, and thus any damage to them due to genetic or environmental factors leads to irreversible sensorineural hearing loss (SNHL) [ 2 ]. However, currently, there is no effective treatment to biologically replace damaged SGNs.…”
Section: Introductionmentioning
confidence: 99%
“…In the postnatal cochlea, GCs are involved in promoting the development and survival of SGNs by providing neuregulin and neurotrophic support [ [10] , [11] , [12] ], as well as maintaining the proper function of SGN [ 13 ]. Recently, studies have identified the neonatal inner ear GCs as a potential source of neural stem/progenitor cells (NSPs) for SGN regeneration [ 2 ]. For example, the quiescent GCs could be activated and initiate proliferation after SGN degeneration [ 7 , 14 ], several subtypes of GCs, such as proteolipid protein (PLP1)-positive GCs [ 4 ], Sox2-positive glial population [ 15 ], can give rise to neurons and GCs, but not HCs, in vitro or in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have uncovered some promising results in SGNs regeneration, including the differentiation of exogenous stem cells into SGNs and the reprogramming of endogenous glial cells (GCs) in the inner ear 10 . GCs in the inner ear include Schwann cells, which exist along the neuronal bers, and satellite cells, which surround and myelinate ganglionic neuronal cell bodies 11 .…”
Section: Introductionmentioning
confidence: 99%